Biomass burning and carbon monoxide patterns in Brazil during the extreme drought years of 2005, 2010, and 2015. (December 2018) - Ribeiro, I.O.; Andreoli, R.V.; Kayano, M.T.; Sousa, T.R.; Medeiros, A.S.; Godoi, R.H.M.; Godoi, A.F.L.; Duvoisin, S.; Martin, S.T.; Souza, R.A.F.
Abstract: In the 21st century, severe droughts associated with climate change will increase biomass burning (BB) in Brazil caused by the human activities. Recent droughts, especially in 2005, 2010, and 2015, caused strong socioeconomic and environmental impacts. The 2015 drought considered the most severe since 1901, surpassed the 2005 and 2010 events in respect to area and duration. Herein, based on satellite data, the 2005, 2010 and 2015 drought impacts on wildfire episodes and carbon monoxide (CO) variability during the dry and the dry-to-wet transition seasons were examined. The BB occurrences in the dry season were fewer during 2015 than during 2005 (−44%) and 2010 (−47%). Contrasting, the BB events in the dry-to-wet transition season, were higher during 2015 than during 2005 (+192%) and 2010 (+332%). The BB outbreaks were concentrated in the southern and southwestern Amazon during 2005, in the Cerrado region during 2010, and mainly in the central and northern Amazon during 2015, an area normally with few fires. The CO concentration showed positive variations (up to +30%) occurred in the southern Amazon and central Brazil during the 2005 and 2010 dry seasons, and north of 20 °S during the 2015–2016 dry-to-wet transition season. The BB outbreaks and the CO emissions showed a considerable spatiotemporal variability among the droughts of 2005, 2010, and 2016, first of them driven by local conditions in the tropical North Atlantic (TNA), characterized by warm than normal sea surface waters and the other two by the El Niño occurrences. Graphical abstract: Image Abstract : For the 2015 drought, the number of BB events remained high during the dry-to-wet transition season and affected northern regions where fires are normally few.